Uso do Instagram pelo sistema de justiça brasileiro: análise dos perfis do TJ, TCE e TRE do Tocantins - Oliveira, Charlyne Sueste de (2024)
This research seeks to understand how Instagram is used by the justice system of Tocantins as a strategy for the optmization of public communication. Aspects such as the content, the formats of the posts, the visible engagement, volume and periodicity of publications, the interaction of the profile with its audience in responses to comments and the density of the social capital are the targets of this research. In total, 142 feed posts are analyzed in the period from May 1 to May 31, 2023, of which 25 posts on the TCE-TO profile, 80 posts on the TJ-TO and 37 posts on the TRE-TO. The posts were collected manually in the same time period. The Content Analysis is used as a research analysis method, considering the objectivity, systematization and data inference. The most relevant result of this study is the diversity of strategies adopted in each Court in the management of Instagram profiles, with high variation between qualitative and quantitative data. We also verifiy the difference in the interaction with the followers. There is a huge difference among the social capital observed in the TCE-TO profile compare to the others. In conclusion, we can say that the use of Instagram in the three profiles is mainly to publicize information, it is not a priorit to maintein a relationship and dialogue with society.